Integrated physiological, biochemical, and molecular analysis of drought tolerance in soybean cultivars - Alghabari, Fahad M. (Frontiers in Plant Science, 2026)
Drought stress is an important constraint to soybean (Glycine max L. Merr.) production, specifically in arid and semi-arid regions. This study integrated physiological, biochemical, and molecular approaches to elucidate the adaptive mechanisms of soybean genotypes against drought stress. Seven genotypes, four tolerant, ‘Ajmeri’, ‘NARC-21’, ‘DMX4561’ and ‘Rawal’, and three susceptible ‘Anjasmoro’, ‘Grobogan’, ‘Dering-1’ were evaluated under control and drought conditions in a pot experiment conducted under controlled conditions. Physiological traits, including relative water content (RWC), chlorophyll content, photosynthetic rate (Pn), and cell membrane stability (CMS), were quantified alongside biochemical indicators such as proline, glycine betaine (GB), and antioxidant enzyme activities. The relative expression of drought-responsive genes, GmDREB2, GmLEA-D11, GmP5CS, GmBADH2, GmSOD1, GmCAT1, GmPOD1, GmPIP2;9, GmCHLG was conducted via qRT-PCR. Results indicated that tolerant genotypes kept higher RWC (>80%), chlorophyll (≥1.73 g g−1 FW), Pn (≥30 μmol m−2 s−1), and CMS (>70%) under drought. They also accumulated more proline (up to 47.5 µg g−1 FW) and GB (up to 157 µg g−1 FW). The activities of antioxidant enzymes, in tolerant genotypes were markedly higher (CAT up to 15.3 U mg−1 protein; SOD >50 U mg−1 protein) than in susceptible genotypes. Besides, the multivariate analyses (correlation, PCA, hierarchical clustering) grouped tolerant genotypes to osmolytes (proline, GB), antioxidant enzymes, and physiological traits, proving strong drought trait association. The expression analysis showed high upregulation of stress-related genes (e.g., GmP5CS ~3.8-fold; GmBADH2 ~3.4-fold; GmSOD1 ~3.5-fold) in tolerant genotypes, rectified the physiochemical findings. Overall, these results proved that drought tolerance in soybean is regulated by the co-ordination of osmolytic adjustment, enhanced antioxidant activities, maintenance of photosynthetic traits, and transcriptional activation of stress-responsive genes. The identified tolerant genotypes will serve as promising breeding resources for the development of stress-tolerant soybean cultivars.